2018
DOI: 10.3389/fonc.2018.00488
|View full text |Cite
|
Sign up to set email alerts
|

CD44 Expression Profile Varies According to Maturational Subtypes and Molecular Profiles of Pediatric T-Cell Lymphoblastic Leukemia

Abstract: CD44 is a glycoprotein expressed in leucocytes and a marker of leukemia-initiating cells, being shown to be important in the pathogenesis of T cell acute lymphoblastic leukemia (T-ALL). In this study, we have (i) identified the aberrant antigenic pattern of CD44 and its isoform CD44v6 in T-ALL; (ii) tested the association with different T-cell subtypes and genomic alterations; (iii) identified the impact of CD44 status in T-ALL outcome. Samples from 184 patients (123 T-ALL and 61 AML; <19 years) were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…Recently, we have demonstrated the aberrant antigenic pattern of CD44 in T-ALL according to T-ALL cell subtypes. CD44 expression in mature subtypes seems to be influenced by genomic alterations in NOTCH1 signaling pathway validating the studies performed in an animal model and/or in co-cultures of human cell lines (16, 26). In the cortical stage, double positivity for CD4/CD8 was found in the majority of T-ALL cases, while the mature T-ALL subtypes were carefully subdivided according to CD4 and CD8 expression (DP, SP and DN) (27, 28).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Recently, we have demonstrated the aberrant antigenic pattern of CD44 in T-ALL according to T-ALL cell subtypes. CD44 expression in mature subtypes seems to be influenced by genomic alterations in NOTCH1 signaling pathway validating the studies performed in an animal model and/or in co-cultures of human cell lines (16, 26). In the cortical stage, double positivity for CD4/CD8 was found in the majority of T-ALL cases, while the mature T-ALL subtypes were carefully subdivided according to CD4 and CD8 expression (DP, SP and DN) (27, 28).…”
Section: Discussionsupporting
confidence: 71%
“…In all cases, the immunophenotyping by multiparametric flow cytometry was performed utilizing the panel of monoclonal antibodies in Supplementary Table 1. FACS Calibur and FACS Canto II flow cytometers (Becton, Dickinson, and Company, CA, USA) were used for the sample acquisition and all the immunophenotypic analyses were performed in the Infinicyt™ program version 1.8 (Cytognos—Salamanca—Spain), according to previously published procedures (16, 17). A sample was considered positive for a marker when at least 20% of lymphoblasts in a CD45 low / intermediate gate had its expression.…”
Section: Methodsmentioning
confidence: 99%
“…By using a novel mouse model of human T-ALL pathogenesis [ 276 ], this work showed that CD44 is a direct transcriptional target of NOTCH1, which is upregulated in NOTCH1-induced preleukemic blasts, facilitating their engraftment into the bone marrow niche, and supporting the LIC potential of T-ALL [ 276 ]. These results indicate that CD44 upregulation is a key event of T-cell leukemogenesis, a finding that concurs with the fact that T-ALL patients commonly display an aberrant expression of CD44 in leukemic blasts [ 277 ]. Although no link of CD44 expression with prognosis and overall survival of T-ALL patients has been established [ 277 ], CD44 contributes to T-ALL maintenance and progression, likely by regulating LIC potential [ 278 ], as proved by anti-CD44 mAb administration in a PDX T-ALL model [ 276 ].…”
Section: Potential New Targets For T-all Immunotherapysupporting
confidence: 80%
“…These results indicate that CD44 upregulation is a key event of T-cell leukemogenesis, a finding that concurs with the fact that T-ALL patients commonly display an aberrant expression of CD44 in leukemic blasts [ 277 ]. Although no link of CD44 expression with prognosis and overall survival of T-ALL patients has been established [ 277 ], CD44 contributes to T-ALL maintenance and progression, likely by regulating LIC potential [ 278 ], as proved by anti-CD44 mAb administration in a PDX T-ALL model [ 276 ]. CD44 expression is also upregulated in Notch1-induced T-ALL leukemic cells treated with chemotherapeutic drugs, such as doxorubicin and dexamethasone, and contributes to T-ALL chemoresistance by modulating intracellular drug efflux [ 279 ].…”
Section: Potential New Targets For T-all Immunotherapysupporting
confidence: 80%
“…At present, CD44 was identified as a stemness-related gene of several cancers including glioblastoma, breast cancer, hepatocellular carcinoma, colorectal cancer and acute myeloid leukemia [40]. Significantly higher expression levels were observed in patients with ALL compared with umbilical cord blood precursor cells [41] and contributed to chemoresistance by increasing drug efflux [42]. Interestingly, the gene expression level of CD44 in ALL cases with MLL-r was much greater than that in ALL cases without MLL-r [43,44], which was consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%